2016
DOI: 10.1161/hypertensionaha.115.05924
|View full text |Cite
|
Sign up to set email alerts
|

Renal Resistive Index Predicts Postoperative Blood Pressure Outcome in Primary Aldosteronism

Abstract: SummaryRemoval of aldosterone-producing adenoma reduces renal resistive index. Preoperative resistive index may predict blood pressure outcome after surgery. Early detection of primary aldosteronism is important for preventing organ damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…16 The resistive indices of main, hilum, and interlobar arteries were significantly reduced 1 month after adrenalectomy and remained stable for 12 months. 16 The resistive indices of main, hilum, and interlobar arteries were significantly reduced 1 month after adrenalectomy and remained stable for 12 months.…”
Section: Rri and S Econdary Hyperten S I Onmentioning
confidence: 89%
See 1 more Smart Citation
“…16 The resistive indices of main, hilum, and interlobar arteries were significantly reduced 1 month after adrenalectomy and remained stable for 12 months. 16 The resistive indices of main, hilum, and interlobar arteries were significantly reduced 1 month after adrenalectomy and remained stable for 12 months.…”
Section: Rri and S Econdary Hyperten S I Onmentioning
confidence: 89%
“…Moreover, regarding the endocrine causes of secondary HTN, a recent study has shown that RRI was significantly higher in patients with aldosteronoma. 16 The resistive indices of main, hilum, and interlobar arteries were significantly reduced 1 month after adrenalectomy and remained stable for 12 months. Of note, the initial RRI was significantly associated with long-term postoperative resistant HTN.…”
Section: Rri and S Econdary Hyperten S I Onmentioning
confidence: 89%
“…In the present study, we observed that interlobar and arcuate artery resistive index values were significantly increased in type 2 diabetic patients compared with controls and also significantly increased values were observed in microalbuminuric diabetics compared with normoalbuminuric diabetics. A high renal RI may reflect increased stiffness of preglomerular arteries and increased intrarenal vascular resistance, including postglomerular circulation [27].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Chapman et al [34] showed that RRI is comparable in patients with EH and hypertensive ADPKD, and recently has been demonstrated that patients with PA have higher RRI, reversible after treatment. [48] The mechanisms by which aldosterone exerts its negative effect include an oxidative stress and an endothelial dysfunction through a decreased synthesis and release of nitric oxide, [27,49] the production of reactive oxygen species mediated by nicotinamide adenine dinucleotide phosphateoxidase-dependent mechanisms, [50] inflammation and fluid retention, determining vascular remodeling, hypertrophy, and fibrosis. [5154] Furthermore, aldosterone seems also involved in the development of metabolic syndrome, dyslipidemia, and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%